(untitled) (Journal of Economic Additions, 2026)
Addressing the dichotomy between food security and consumer safety, this study analyzes the tensions between agricultural expansion and public health risks associated with modern biotechnologies. Utilizing a descriptive-analytical approach, the findings indicate that major exporters, notably Brazil and Argentina, frequently prioritize economic returns over rigorous safety standards. The research identifies a persistent global regulatory deficit in monitoring chemical inputs and genetically modified crops within transnational supply chains. Consequently, it recommends the harmonization of international biosafety protocols and the strengthening of multilateral oversight to ensure that food security strategies do not compromise long-term consumer health. Jel Classification Codes: Q18, Q1, Q100,F1